Analysis of Capital Budgeting Decision-Making Using the Electre Decision Support System Method (Case Study on Export-Oriented Msmes: PT. Mekar Saluyu Group) - Amira, Khansa Indra (Jurnal Multidisiplin Indonesia, 2024)
The era of globalization brought about a significant transformation in international trade, allowing for greater participation of MSMEs. However, even though Indonesia has the largest number of MSMEs in ASEAN, the percentage of MSMEs involved in exports is still low. Various factors hinder the expansion of MSMEs to the international market, including financial management constraints. To overcome these challenges, strengthening strategies are needed, such as fostering a conducive business environment, increasing access to capital, and developing infrastructure. In the context of financial strengthening, it is important for MSMEs to understand capital financing strategies and financial decision-making. The capital budgeting method is crucial in determining investment projects that can increase profitability and expand business. To facilitate proper decision-making, the use of integrative techniques in capital budgeting is important. One method that can be used is the ELECTRE Decision Support System (SPK), which helps to develop investment alternatives based on certain criteria to facilitate decision-making. This study will apply the capital budgeting method and SPK ELECTRE to assist companies in choosing investment options for curly chili or sweet potato plants using five calculation criteria, this study aims to provide guidance for MSMEs in making the right financial decisions.